TOWARDS MORE INCLUSIVE HEALTHCARE (The Role of Digitalization in Expanding Access and Improving Quality in Indonesia) - Kurnia Dewi, Nina; Aisyah Putri, Siti; Sakti Aditya, Bima (Institut Teknologi Bisnis dan Kesehatan Bhakti Putra Bangsa Indonesia, 2024)
In today's digital era, digitalization of health services is the key to achieving more inclusive services, expanding access, and improving the quality of health services in Indonesia. This article aims to analyze the role of digitalization in responding to such challenges, focusing on the implementation of telemedicine, health applications, and electronic health information systems. Using qualitative and quantitative approaches, the study collected data from a variety of sources, including interviews with health practitioners, surveys of healthcare users, and analysis of health policy documents. The results show that digitalization has had a positive impact on the accessibility of health services, especially in remote areas and for community groups who previously faced barriers in accessing health services. Digitalization also contributes to improving service quality through the provision of more accurate and faster health information. However, the study also identified a number of barriers, including technology infrastructure issues, digital literacy among users, and concerns over data privacy and security. This article provides recommendations for addressing these barriers, including increased investment in technology infrastructure, digital literacy training programs, and the development of stronger policies to protect the privacy and security of user data. This research confirms the importance of digitalization integration in Indonesia's health system as a strategic step towards more inclusive and quality health services.